2020
DOI: 10.1002/rcm.8565
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and sensitive analytical procedure for biomonitoring of organophosphate pesticide metabolites in human urine samples using a vortex‐assisted salt‐induced liquid–liquid microextraction technique coupled with ultra‐high‐performance liquid chromatography/tandem mass spectrometry

Abstract: Rationale Organophosphate pesticides (OPPs) are the most commonly used insecticides around the world in various agricultural and domestic practices, and humans are frequently exposed to these hazardous insecticides that can lead to several chronic health effects. Therefore, a fast and sensitive analytical method is required for biomonitoring the markers of OPPs in humans for exposure estimation. In this study, a fast and sensitive analytical procedure was developed for the determination of the metabolites of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The detection of DAP metabolites was made possible by a rapid and straightforward liquid-liquid extraction procedure. In contrast to previous studies, which required 0.5-10 mL of sample and 5-15 mL of solvent for sample extraction, the recovery rate was lower (13-114%) and chromatographic separation was lengthy (10-35 min), with a detection limit of 0.1-6 ng/mL [17,33,37,[40][41][42][43][44][45][46]. With the present method, each sample can be analyzed in only 30 min, making it ideal for laboratories that process a large volume of samples in a short time.…”
Section: Discussionmentioning
confidence: 69%
“…The detection of DAP metabolites was made possible by a rapid and straightforward liquid-liquid extraction procedure. In contrast to previous studies, which required 0.5-10 mL of sample and 5-15 mL of solvent for sample extraction, the recovery rate was lower (13-114%) and chromatographic separation was lengthy (10-35 min), with a detection limit of 0.1-6 ng/mL [17,33,37,[40][41][42][43][44][45][46]. With the present method, each sample can be analyzed in only 30 min, making it ideal for laboratories that process a large volume of samples in a short time.…”
Section: Discussionmentioning
confidence: 69%
“…In Table 5 Comparison of the proposed method with other reported methods. We compared our method with previously reported LC-MS /MS methods and their sample preparation [34][35][36][37][38][39] . This study showed the best extraction procedure for the determination of six OPs metabolites in the urine; we compared the extraction procedure commonly used and also compared the other reported LC-MS/MS method with our method, Our method proved to be more sensitive with detection limits between 0.0201 to 0.0697 ng/mL for all analytes.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, LLE with diethyl ether and ethyl acetate, alongside salting-out assisted extraction with MgSO 4 and NaCl, also adopting HILIC chromatography but with a Hypersil Gold HILIC column, was assessed for the same 6 DAPs ( 95 ). In a separate investigation, five DAPs were determined using VALLME with ethyl acetate and (NH 4 ) 2 SO 4 , however employing an Inspire C18 column for separation ( 96 ).…”
Section: Methods and Techniquesmentioning
confidence: 99%